INVESTMENT POTENTIAL OF UKRAINE UNDER CURRENT CONDITIONS - Syrotyuk , Г. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
The article studies investment potential of the country and identifies constituents of that concept. The work outlines preconditions for attracting direct foreign investments in the economy of Ukraine that is crucial for the economy recovery after the Russian-Ukrainian war. The authors analyze the Index of investment attractiveness of Ukraine and determine that the investment climate in Ukraine is unfavorable and is getting worse in the dynamics. It is mentioned that the main factors which negatively influence the investment attractiveness are hostilities in the country, COVID-19 pandemic, corruption and imperfect juridical system. The researchers analyze income of foreign investments in Ukraine and from Ukraine, and outline dynamics of the flows of foreign investments for 7-year period, as well as the factors influencing them. It is determined that in spite of reduction in the amount of foreign investments, their importance as a source of formation of the Ukraine’s investment potential is growing. The work outlines tools of the state support, particularly the simplified procedure to transfer to a single tax, the simplified mechanism of reporting, better access to crediting. There are several kinds of risks, which should be currently considered by investors, namely economic, political, safety and foreign exchange market. It is substantiated that during the war, the situation can significantly change in terms of the economic sectors, and, therefore, investors should diversify their portfolio, investing into several branches. The research proves importance of attracting foreign investments for the national economy in the long term. The authors identify prerequisites for the foreign investors put money in the economy of Ukraine, including creation of a powerful regulatory base, which is able to protect and secure investments; introduction of the instruments of tokenization of assets and development of the market of virtual assets. According to the results of the conducted research, some ways to improve investment attractiveness of Ukraine under current conditions are proposed.